2009
DOI: 10.1124/dmd.109.027904
|View full text |Cite
|
Sign up to set email alerts
|

The Ontogeny, Distribution, and Regulation of Alcohol Dehydrogenase 3: Implications for Pulmonary Physiology

Abstract: ABSTRACT:Class III alcohol dehydrogenase (ADH3), also termed formaldehyde dehydrogenase or S-nitrosoglutathione reductase, plays a critical role in the enzymatic oxidation of formaldehyde and reduction of nitrosothiols that regulate bronchial tone. Considering reported associations between formaldehyde vapor exposure and childhood asthma risk, and thus potential involvement of ADH3, we reviewed the ontogeny, distribution, and regulation of mammalian ADH3. Recent studies indicate that multiple biological and ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 100 publications
0
7
0
Order By: Relevance
“…Consistent with these human studies, the results of our animal studies indicated that FA exposure significantly increased the airway resistance during inspiration and expiration in non-sensitized BALB/c and C57BL/6 mice. It is likely that formaldehyde may contribute to the regulation of S-nitrosoglutathione (GSNO) metabolism and thus influence smooth muscle tone in the airways [24]. GSNO is considered an endogenous bronchodilator involved in airway smooth muscle relaxation [25].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with these human studies, the results of our animal studies indicated that FA exposure significantly increased the airway resistance during inspiration and expiration in non-sensitized BALB/c and C57BL/6 mice. It is likely that formaldehyde may contribute to the regulation of S-nitrosoglutathione (GSNO) metabolism and thus influence smooth muscle tone in the airways [24]. GSNO is considered an endogenous bronchodilator involved in airway smooth muscle relaxation [25].…”
Section: Discussionmentioning
confidence: 99%
“…Active research is presently underway to determine whether ADH3, also termed formaldehyde dehydrogenase (FDH) or S-nitrosoglutathione reductase (GNSO), which has been shown to play a key role in the enzymatic oxidation of formaldehyde and reduction of nitrosothiols that regulate bronchial tone, may also play a role in the risk of asthma (Staab et al, 2009; Thompson et al, 2009). However, it is presently unknown if there are polymorphic forms of ADH3, which would suggest a hypothetical possibility of differential sensitivity to formaldehyde effects on bronchial sensitivity.…”
Section: Iiisensory Irritationmentioning
confidence: 99%
“…[20][21][22] Interestingly, studies in mouse and rat embryos show that while GSNOR is active during induction of the mammalian cardiogenic program, the developing heart exhibits the lowest GSNOR activity compared with other embryonic tissues. 23,24 Moreover, mice deficient in GSNOR develop normally 25 but are characterized by a high propensity for postnatal hepatocarcinogenesis (HCC). 26 Remarkably, they also exhibit a profound capacity for repairing liver 27 and heart injury.…”
mentioning
confidence: 99%